Proposed development strategy for sate virgin - Yodi Rizkyardi, Mohammad; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2016)
Abstract - Sate Virgin is authentic sate restaurant specialty in tegal goat sate that found by Mr Koma in 2013 located in Bekasi area. In 2015, sate Virgin move to a new location and since then Sate Virgin business is growing in revenue increases and customer number increases. Mr Koma felt that Sate Virgin has huge potential and need to be growth. Good strategy formulation is needed to decide the most suitable direction for Sate Virgin growth in the future. To develop the strategy, first is to analyze the external and internal condition. For external condition analysis, using PEST analysis, Porter’s Five Forces and competitor analysis. For internal condition, using VRIO model, financial analysis and business model canvas. Both analyses then form the SWOT analysis for become the basis of strategy formulation. For company strategy, using SPACE matrix and generate two alternative strategy which is intensive and integrative strategy. In order to determine which strategy is suitable for Sate Virgin, QSPM method calculation is being used. The result from the QSPM calculation showing that intensive strategy is more suitable for Sate Virgin. The TOWS matrix is use for generating alternative action of strategy that can be grouping into company function. Diamond strategy is use to describe both strategy comprehensively and last is to proposed new business model canvas. Strategic steps from intensive strategy, which is market penetration, market development and product development, can be implement by Sate Virgin as its development direction to achieve Sate Virgin business sustainability. Keywords: restaurant business, intensive strategy, diamond strategy